Substituição da carne mecanicamente separada por diferentes concentrações de hidrolisado proteico em mortadela - Cavalheiro, Carlos Pasqualin (2012)
The objective of this study was to develop a liquid protein hydrolysate from Mechanically Deboned Chicken Meat (MDCM) by enzymatic hydrolysis and to evaluate the addition of different concentrations (10, 20 and 30%) in a reduced-fat mortadella-type sausage. First, it was evaluated the addition of BHT antioxidant (0.01%) and curing salts (0.25%) in the production of protein hydrolysate at different hydrolysis times (5, 15, 30 and 60 minutes) in order to reduce lipid oxidation and brownish color formation. There were evaluated the degree of hydrolysis, pH, proximate composition, lipid oxidation and instrumental color. It was observed that the addition of BHT antioxidant and curing salts did not affect the degree of hydrolysis at 60 minutes. The pH was similar to the MDCM and the proximate composition was not affected by the hydrolysis process or by the addition of BHT antioxidant and curing salts. However, there was a synergistic action between the BHT antioxidant and the curing salts in lipid oxidation prevention of the hydrolysates during the whole period of hydrolysis. Also, there was observed a reduction in the formation of a brownish color mainly by the use of curing salts, evidenced by high levels of values of a* (redness). Subsequently, there was evaluated the addition of different concentrations protein hydrolysate containing BHT antioxidant and curing salts in a reduced-fat mortadella-type sausage. Thus, four treatments were made containing 0, 10, 20 and 30% of MDCM protein hydrolysate. There were evaluated the proximate composition, pH, lipid oxidation, colorimetric parameters, texture profile and microbiological and sensory characteristics during 60 days of storage at 4 ºC. The proximate composition, pH and microbiological characteristics were considered normal for this kind of product. The values of lipid oxidation of products containing MDCM protein hydrolysate increased up to 30th day of storage with subsequent decrease until the end of the storage period (60 days). The products containing MDCM protein hydrolysate had low values of L* (lightness) and a* (redness), higher lipid oxidation and soft textured, evidenced both by the panelists and by instrumental texture profile. The addition of up to 10% protein hydrolysate proved to be viable in the production of reduced-fat mortadella-type sausage, showing quality characteristics closer to the control treatment.